Analisis Kualitatif dan Kuantitatif Boraks Pada Cincau Hitam Yang Beredar di Tangerang Selatan dengan Metode Asidimetri - Beny Maulana Satria; Nur Hasanah; Nurul Istiqomah (Edu Masda Journal, 2019)
In the state of indonesia borax had been used here as an ingredient of a food preservative .From the results of testing the sample at lab where internal conditions food and drug monitoring agency ( from food and medicine supervision ) who conducted in a number of 2011 included the sites of Bandar Lampung , Jakarta , garbage generated by Bandung residents , Semarang the capital city of , Yogyakarta in central java , Surabaya , Mataram , and Makassar to be channeled has been carried out the sample collection and examination on lab where internal conditions a number of sample 20,511 food was laid aside as .The whole purpose of the of this research is to know if there are the moisture content of borax in black jellyfish which circulates in south tangerang .Was used in the study a method of titration acidimetry with the process of over the withdrawal of funds at random sample 10 black jellyfish from street vendors , the market and supermarkets which circulates in South Tangerang. The results of the study borax in black cincau circulating in south tangerang decay 6 is to test samples containing preservative, other additional and materials in the flame is 4 sample containing borax and showed the fiery, green color blue and blue, greenish in titrations acidimetry 10 containing borax. sample isThe research is known the borax and extra ingredient in black cincau circulating in south tangerang.The lowest in the borax cincau black 22,3 / grams as the highest kg and kg 33,6 / grams.  Keywords    :